Multi-axis low-cycle creep/fatigue life prediction of high-pressure turbine blades based on a new critical plane damage parameter. (December 2019) - Huo, Junzhou; Sun, Debin; Wu, Hanyang; Wang, Weizheng; Xue, lin
Abstract: To study the multi-axis low-cycle creep/fatigue life of high-pressure turbine blades, a multi-axis low-cycle fatigue life prediction model based on a new critical plane damage parameter is proposed in this paper. Firstly, based on the thermal-structural coupling analysis of high-pressure turbine blades, the law of stress-strain distribution under the complex load of centrifugal load, temperature load and the aerodynamic load is obtained. Secondly, the multi-axis low-cycle fatigue life prediction model and the L-M equation are applied to predict the fatigue life and creep life of blade respectively. Furthermore, different experimental loading schemes are used to study the fatigue damage mechanism for the creep/fatigue interaction under high temperature condition, and a creep/fatigue interaction life prediction model is simultaneously provided. And finally, the experiment results demonstrate the rationality of the multi-axis low-cycle fatigue life prediction model and the creep/fatigue interaction should not be ignored. Highlights: A multi-axis low-cycle fatigue life prediction model based on a new critical plane damage parameter is proposed. The effects of main cycle and secondary cycle on multi-axis low cycle fatigue life are considered simultaneously. A creep/fatigue interaction life prediction model is provided and calculate the creep/fatigue interaction life of the blade.